An in-line digestive cartridge increases enteral fat and vitamin absorption in a porcine model of short bowel syndrome. Issue 5 (May 2022) - Tsikis, S.T.; Fligor, S.C.; Secor, J.D.; Yu, L.J.; Pan, A.; Mitchell, P.D.; Loring, G.; First, E.; Nedder, A.P.; Grammer, R.M.; Pattison, B.; Gura, K.M.; et al.
Summary: Background & aims: Short bowel syndrome (SBS) occurs after intestinal loss resulting in parenteral nutrition dependence and micronutrient deficiencies, which may lead to life-limiting complications. ALC-078 is a cartridge containing immobilized lipase that connects in-line with enteral feeding sets and digests fats in enteral nutrition (EN). In this study, we evaluate the efficacy of ALC-078 to improve fat and nutrient absorption in a porcine SBS model. Methods: Fifteen male Yorkshire piglets were assessed. Animals were randomized to no intestinal resection (n = 5), 75% resection (n = 5), or 75% resection + ALC-078 (n = 5). After recovery, animals were treated for 14 days. Piglets received 60% of nutrition from continuous EN and 40% from chow. The degree of fat malabsorption was determined by the coefficient of fat absorption (CFA) following a 72-h stool collection. Body weight, fat-soluble vitamins, and nutritional markers were assessed. Results: Adverse events were similar across the three groups ( P = 1.00). ALC-078-treated animals had similar weight gain compared to resected piglets. Resected animals had a lower CFA compared to unresected controls (79.3% vs. 95.2%, P = 0.01) while there was no significant difference in the ALC-078 animals (87.1% vs. 95.2%, P = 0.19). Between Study Days 1 and 15, ALC-078 animals had increased concentrations of vitamin D (12.2 vs. 8.7 ng/mL, P = 0.0006), and vitamin E (4.3 vs. 2.5 mg/L, P = 0.03). These markers did not significantly change in untreated resected animals. Conclusion: ALC-078 increases the absorption of fat-soluble vitamins and may improve fat malabsorption. Future studies should determine whether ALC-078 can reduce PN dependence and if these findings translate to human patients with SBS.